PENGARUH KOMPENSASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWA PADA PT. MULIA SUKSES JAYA DI BOGOR - Ridwan, Muhammad; Muharomi, Ahmad (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2019)
Every company wants the goals set can be achieved in a timely manner. Therefore, it is necessary to have good management of human resources owned by a company. In this study to determine the effect of variables with the title